479 Retrospective review of hematological toxicity of chemoradiotherapy in locally advanced cervical cancers. (4th December 2020) - Perera, Jananie; Eminowicz, Gemma
Abstract : Introduction/Background: Concurrent chemoradiotherapy with cisplatin is the standard of care for locally advanced cervical carcinoma. University college London hospital (UCLH) treats patients with cervical cancer with VMAT as a standard practice due to proven advantages. (1, 2) However data on haematological toxicity appear limited. We therefore reviewed the haematological toxicity in our patients treated with VMAT. Methodology: Retrospective review of electronic records of all patients with cervical cancer who had VMAT at UCLH up to 31st May 2020 was conducted. Patient with non-carcinoma histology, post-operative treatments, recurrences, no concurrent cisplatin and those started on granulocyte colony stimulating factors (G-CSF) prior to radiotherapy were excluded. Haematological parameters were categorized by CTCAE version 5 haematological toxicity criteria. Findings were compared to published haematological toxicity data for cervical cancer IMRT or VMAT treatments with concurrent cisplatin using predetermined comparator values. (3–13) Results: 38 patients received VMAT treatments and 30 patients fulfilled inclusion criteria. 50% had FIGO (2009) stage IIB disease. 36.7% had regional lymphadenopathy. Neoadjuvant chemotherapy with weekly paclitaxel and carboplatin was received by 70%. 86.7% completed 5 or more cycles of cisplatin. 63.3% were prescribed 50.4Gy in 28 fractions to the pelvis, remainder received higher doses as simultaneous lymph node boosts. 23.3% received para aortic strip extended field radiation. Maximum haematological toxicity observed is given in table 1 . Two had received less than 5 cycles of cisplatin due to thrombocytopenia, while 2 others for non-haematological toxicity. 3 others have managed 5 cycles with G CSF support Table 2 gives a comparison with published haematological toxicity data for cervical cancer IMRT/VMAT. Grade 4 lymphopenia was significantly associated with having extended field radiotherapy (p = 0.029) and Grade 3 or more thrombocytopenia with induction chemotherapy (p=0.021). No associations could be elicited with stage 111c or higher disease, having lymph node boost or dose more than 50.4Gy. Conclusion: Significantly worse Thrombocytopenia and lymphopenia was seen compared to published data. However, there is heterogeneity in patient populations and treatments within existing studies with little data on the effects of extended field radiotherapy, lymphnode boosts or induction chemotherapy. We are therefore conducting a dosimetric analysis to investigate if bone marrow sparing VMAT could reduce the toxicity in this population of patients. Disclosures: None.